2014
DOI: 10.1038/srep07321
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of superconducting critical temperature increase in electromagnetic metamaterials

Abstract: A recent proposal that the metamaterial approach to dielectric response engineering may increase the critical temperature of a composite superconductor-dielectric metamaterial has been tested in experiments with compressed mixtures of tin and barium titanate nanoparticles of varying composition. An increase of the critical temperature of the order of ΔT ~ 0.15 K compared to bulk tin has been observed for 40% volume fraction of barium titanate nanoparticles. Similar results were also obtained with compressed mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 20 publications
10
63
0
Order By: Relevance
“…In both cases  eff (q,) may become small and negative in substantial portions or the relevant fourmomentum (q,) space, leading to enhancement of electron pairing interaction. This approach has been verified in experiments with compressed mixtures of tin and barium titanate nanoparticles of varying composition [2]. An increase of the critical temperature of the order of T c ~ 0.15 K compared to bulk tin has been observed for 40% volume fraction of barium titanate nanoparticles, which corresponds to ENZ conditions.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…In both cases  eff (q,) may become small and negative in substantial portions or the relevant fourmomentum (q,) space, leading to enhancement of electron pairing interaction. This approach has been verified in experiments with compressed mixtures of tin and barium titanate nanoparticles of varying composition [2]. An increase of the critical temperature of the order of T c ~ 0.15 K compared to bulk tin has been observed for 40% volume fraction of barium titanate nanoparticles, which corresponds to ENZ conditions.…”
Section: Introductionmentioning
confidence: 67%
“…Namely, we have demonstrated that the metamaterial approach to dielectric response engineering may increase the critical temperature of a composite superconductor-dielectric metamaterial [1,2]. Superconducting properties of a material, such as electronelectron interactions and the critical temperature of superconducting transition may be expressed via the effective dielectric response function  eff (q,) of the material [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this task is much more challenging than typical applications of superconducting metamaterials suggested so far [48], which only deal with metamaterial engineering on the scales which are much smaller than the microwave or RF wavelength. Nevertheless, these experimental difficulties have been overcome in two recent successful demonstrations of metamaterial superconductors [49,50]. In the case of aluminium, its superconducting temperature was more than tripled by the metamaterial engineering [50].…”
Section: Superconducting Hyperbolic Metamaterialsmentioning
confidence: 99%
“…The strong enhancement of superconducting T c in the mono-layer FeAs or FeSe on SrTiO 3 substrate is deeply related to the interfacial optical phonon mode [11,[24][25][26][27]. Attempts of using Boson other than phonons, such as the plasma in meta-materials, to mediate the electron-electron attraction also appear promising [28,29].…”
Section: Introductionmentioning
confidence: 99%